THE IMPORTANCE OF LEARNING ENGLISH IN TODAY`S WORLD (Ustozlar uchun, 2026)
English has become one of the world`s dominant languages today,significantly influencing global communication,science, business and technological development. It has not only become a tool in international cooperation and education but has also become an integral part of society through culture,art and mass media. This study reveals that learning English is not just an advantage-but it is a fundamental necessity.